Breast cancer during pregnancy: epidemiology, phenotypes, presentation during pregnancy and therapeutic modalities. (June 2022) - Boere, Ingrid; Lok, Christianne; Poortmans, Philip; Koppert, Linetta; Painter, Rebecca; vd Heuvel-Eibrink, Marry M.; Amant, Frederic
Abstract: Although it is uncommon in general, breast cancer is the most commonly diagnosed cancer during pregnancy. While treatment for pregnant patients should adhere to treatment guidelines for non-pregnant patients, there exist specific considerations concerning diagnosis, staging, oncological treatment, and obstetrical care. Imaging and staging are preferably performed using breast ultrasound and mammography. Other ionizing radiation imaging modalities, including computed tomography (CT) and Positron Emission Tomography/ Computed Tomography (PET/CT), can be selectively performed when the estimated benefit for the mother outweighs the risks to the foetus, e.g., when the results will change clinical management. MRI is appropriate to stage for distant disease on the indication. Breast cancer during pregnancy is less often hormone receptor-positive and more frequently triple-negative breast cancer compared to age-matched controls. The basic principle is that women should receive state-of-the-art oncological treatment without delay if possible and that the pregnancy should be maintained as long as possible. Treatment strategy should be multidisciplinary defined, carefully weighing the selection, sequence, and timing of treatment modalities depending on patient-, tumour-, and pregnancy-related characteristics, as well as patient preferences. Initiating cancer treatment during pregnancy often decreases the risks of early delivery and prematurity. Breast cancer surgery is possible during all trimesters. Radiotherapy is possible during pregnancy in the first half of pregnancy. Chemotherapy can be safely administered starting from 12 weeks of gestational age, but endocrine and HER2 targeted therapy are contraindicated throughout the whole pregnancy. Importantly, foetal growth should be monitored and long-term follow-up of the children is encouraged in dedicated centres. Highlights: Pregnant women with breast cancer should receive optimal oncological treatment. Treatment should follow protocols outside pregnancy as much as possible. Modality and timing of treatment should be determined multidisciplinary. Locoregional staging is done by US and mammography, similar to outside pregnancy. Women with breast cancer during pregnancy should be referred for genetic counselling.